Phytoalexins of the Pyrinae: Biphenyls and dibenzofurans - Chizzali, Cornelia; Beerhues, Ludger (Beilstein Journal of Organic Chemistry, 2012)
Biphenyls and dibenzofurans are the phytoalexins of the Pyrinae, a subtribe of the plant family Rosaceae. The Pyrinae correspond to the long-recognized Maloideae. Economically valuable species of the Pyrinae are apples and pears. Biphenyls and dibenzofurans are formed de novo in response to infection by bacterial and fungal pathogens. The inducible defense compounds were also produced in cell suspension cultures after treatment with biotic and abiotic elicitors. The antimicrobial activity of the phytoalexins was demonstrated. To date, 10 biphenyls and 17 dibenzofurans were isolated from 14 of the 30 Pyrinae genera. The most widely distributed compounds are the biphenyl aucuparin and the dibenzofuran γ-cotonefuran. The biosynthesis of the two classes of defense compounds is not well understood, despite the importance of the fruit crops. More recent studies have revealed simultaneous accumulation of biphenyls and dibenzofurans, suggesting sequential, rather than the previously proposed parallel, biosynthetic pathways. Elicitor-treated cell cultures of Sorbus aucuparia served as a model system for studying phytoalexin metabolism. The key enzyme that forms the carbon skeleton is biphenyl synthase. The starter substrate for this type-III polyketide synthase is benzoyl-CoA. In apples, biphenyl synthase is encoded by a gene family, members of which are differentially regulated. Metabolism of the phytoalexins may provide new tools for designing disease control strategies for fruit trees of the Pyrinae subtribe.
Keywords: biphenyls; dibenzofurans; phytoalexins; Pyrinae; Sorbus aucuparia